The fashion file : advice, tips, and inspiration from the costume designer of Mad men - Bryant, Janie; Harel, Monica Corcoran (New York, NY : Grand Central Life & Style, 2010)
Offers readers a peek into the dressing room of the hit television show "Mad Men," revealing the design process behind the characters' looks and showing every woman how to find her own leading lady style.
Keywords: Clothing and dress; Costume design -- United States; Mad men (Television program)